The Pharmacological and Clinical Effects of Pentoxifylline on Pet Animals - Zagzoug, Aya S.; Khair, Mohamed H.; Mohamed A. Kamel (Journal of Advanced Veterinary Research, 2023)
Plenty of restorative plants including phenols, essential oils, flavonoids, glycosides, and amides, have been assessed for therapeutic effects against several diseases especially liver diseases. Pentoxifylline (PTX), a methyl-xanthine spin-off with a variety of anti-inflammatory and protective actions in animals. PTX has been found effective for many disease conditions. PTX is an immune-modulatory agent used in the treatment of immune-mediated diseases blood vessels inflammation such as cutaneous lupus in canine and navicular disease in horses. It also has hepato-protective effect, so it could be used to treat liver fibrosis and embolism in pet animals. Moreover, it could be used in the treatment of vessels ulcers through improving healing and microcirculation. This review highlighted numerous vital characteristics of PTX and its therapeutic role in various diseases in pet animals. Â